ANALISIS PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Intan Rosemaya Cintya, 12.05.52.0205; Srimindarti, Ceacilia (Students Journal of Accounting and Banking, 2016)
Companies go public have to improve the integrity of the financial statements in order to maintain the confidence of users of financial statements. The sampling method using purposive sampling the study period of 2012 through 2014, with a total sample of 171 manufacturing companies in the Indonesia Stock Exchange. The results showed that institutional ownership, audit committee and independent commissioners significant positive effect on the integrity of financial statements. While managerial ownership and audit quality does not affect the integrity of financial statements. Keywords: Mechanism Of Corporate Governance, Audit Quality And Integrity Of Financial Statements